ment HEALTHY INTERNET DIGITAL LITERACY AS EDUCATION FOR STUDENTS OF SDN 1 PETUGURAN BANJARNEGARA DISTRICT: The internet as a center for searching and providing information is very useful for students in the learning process - Ghufron Zaida Muflih; Muhammad Ilham Sayogi; Rizki Mubarok; Khabib Nasrulloh; Dimas Fernanda (Lembaga Penelitian Pengabdian Masyarakat Penerbitan dan Percetakan Indonesian Scholar Khiar Wafi (LPPMPP IKHAFI), 2024)
The internet as a center for searching and providing information is very useful for students in the learning process. However, a lack of awareness of healthy internet use can lead to unavoidable negative impacts from the internet itself. Likewise with students at SDN 1 Petuguran, Banjarnegara Regency. In order to avoid excessive, uncontrolled and improper use of the internet, it is very important to implement socialization about healthy internet use. This socialization activity aims to increase the knowledge of students at SDN 1 Petuguran Banjarnegara Regency. The results of this activity are first, there is awareness on the part of the school the importance of continuing efforts to control students' use of the Internet so that they become individuals better. Second, this activity is able to increase the knowledge or understanding of students at SDN 1 Petuguran, Banjarnegara Regency about the internet and the impact it has on using the internet, so that students can be wiser in using internet technology. Matter This can be seen from the enthusiasm of the students in the discussion session. Third, collaboration between campuses can be established and school. It is hoped that this socialization activity can be an effort to assist usage Healthy internet in elementary school environments. Keywords: Healthy Internet, Socialization, Internet